BIM Related Technology Enabled Facility Management for Buildings: Challenges and Potential Research Directions - Le, Hoai Nam; Nham Sy, Trung Kien; Nguyen, Quan; Ta, Ngoc Binh; Tran, Phuong Nam (International Journal of Sustainable Construction Engineering and Technology, 2024)
The operation and maintenance phases of the buildings, featured by great time and cost consumption, always contain a variety of complex issues, risks and uncertainties, all of which significantly impact on buildings’ performance. Many cutting-edge digital technology applications are proposed to effectively manage operation and maintenance tasks, and BIM and BIM-related technologies (such as iBMS, sensors and IoT) stand out as the best options because of their advantages for the information management process. In this research, a literature review on the application of BIM and BIM-related technologies for facilities management was conducted in order to measure the challenges of such technologies’ application and potential research directions toward the topic. The results pointed out a number of issues in terms of BIM enabled facilities management, then discussed on challenges and potential research directions on the BIM-FM system for building sector, including: (1) improving and managing data input quality, (2) identifying frameworks and processes for transferring data between BIM and existing operation management systems with the aid of advanced technologies, and (3) developing completely automated BIM enabled facilities management for the goals of automation and sustainable development.